Advanced cooling techniques of P.V. modules: A state of art - Dwivedi, Pushpendu; Sudhakar, K.; Soni, Archana; Solomin, E; Kirpichnikova, I (Case studies in thermal engineering, 2020)
The efficiency of solar systems, in particular photovoltaic panels, is generally low. The output of the P.V. module is adversely affected by their surface rise in temperature. This increase is associated with the absorbed sunlight that is converted into heat, resulting in reduced power output, energy efficiency, performance and life of the panel. The use of cooling techniques can offer a potential solution to avoid excessive heating of P.V. panels and to reduce cell temperature. This paper presents details of various feasible cooling methods, including novel and advanced solutions for P.V. panels and indicates future trends of research. Different features and capability about each cooling techniques are presented, to provide better insight and valuable guidelines for researchers who intend to study, improve or optimise any type of cooling techniques of P·V. modules.